KONTRIBUSI LIKUIDITAS DAN LEVERAGE TERHADAP HARGA SAHAM DAN PROFITABILITAS PERUSAHAAN MANUFAKTUR - Dwi Susilowati; Suhartono; Juwari; Melda Yulinda; Wiwik Saraswati (Faculty of Economics and Business, Universitas Warmadewa, 2026)
Liquidity contribution is measured by fast ratio and current ratio while Leverage is measured by two indicators Debt to Asset Ratio and Debt to Equity Ratio at stock of prices by mediation using Profitability which is measured using the Return on Asset Ratio and Return on Equity Ratio indicators. Data is taken from financial position reports and annual reports. Observations used 6 manufacturing entities indexed LQ45 manufacturing l of 24 observations. This study of uses method regression analysis tools with a quantitative result using SmartPLS 4. From this study, it is said that liquidity has no effect on probability but liquidity has an effect on stock prices and profitability is not able to mediate the relationship between liquidity and stock prices. While the average has no effect on the stock price, neither can profitability mediate the relationship between leverage and the stock price.